Geographic distribution and supply chain of vultures in Benin, West Africa - Samson Dognimon; Stanislas Zanvo; Chabi A. M. S. Djagoun; Brice Sinsin (Conservation Science and Practice)
Abstract Illegal trade poses a significant threat to African vultures, particularly in Benin, which stands as the second major hotspot for vultures' trade in West Africa. To address gaps in research on distribution, supplying habitat sources and trade dynamics, we conducted semi‐structured interviews with 150 sellers in traditional medicine markets (TMM) and surveyed 590 local residents in villages surrounding five protected areas. We used a chord diagram to visually represent the frequency of reports of countries involved in the trade, and mapped local ecological knowledge (LEK)‐based geographic distribution of vultures across Benin. Our findings revealed that seven West African countries, as well as Cameroon from Central Africa supplied vulture specimens to TMM. We recorded 491 vultures specimens from various species such as Hooded, white‐headed, white‐backed, Rüppell's, Egyptian, and lappet‐faced vulture. Among the six vulture species recorded in TMM, five were still found in Benin, primarily in the north of the country. Our study provides insights into the supply chain and LEK‐based geographic distribution of vultures in Benin. It highlights the pressing need for further research using conventional methods to study the diversity and distribution of vultures in Benin, as well as concerted and coordinated conservation interventions to support vulture populations in the region.